Իրավական հասկացությունները Գրիգոր Տաթևացու «Գիրք քարոզութեան» Ամառան հատորի «Նորին քարոզ վասն տասնաբանեան օրէնս» գլուխներում - Գրիգորյան, Սուսաննա (ԳԱԱ ԼԻ հրատ․)
The “Books of Sermons” of Grigor Tatevatsi, written with the aim of introducing spiritual values into public life, before being written down, were first preached live to the people, and in the chapter “Ten Commandments” dozens of concepts given, being in the layer of commonly used words, were used as legal ones and are used according to all the norms of a legal concept. Рассмотрение правовых понятий литературного наследия Григора Татеваци интересно само по себе, но крайне интересны новые слова, использованные автором в этой области, особенно в юридическом смысле, то есть в данном случае еще и в смысле восприятия тонкостей этих терминах современника. Иногда они содержат историческую информацию, как в случае со словом «гитвор» "githwor" - виновный, преступник).
Keywords: Հայոց լեզու; Լեզվաբանություն